In-Breeding Effect on Performance of Rhode Island Chickens Selected for Part-Period Egg Production - Nwagu, B.I.; Olorunju, S.A.S.; Oni, O.O.; Eduvie, L.O.; Adeyinka, I.A.; Sekoni, A.A.; Abeke, F.O. (International Journal of Poultry Science, 2006)
Data from 4336 pullets progeny of 144 sires and 779 dams for strain A and 4843 pullets, progeny of 158 sires and 1108 dams for strain B belonging to 5 generations under selection for part-period egg production to 280 days of age were used for this study. The number of pullets housed at about 18weeks per population ranged from 326 and 1000 per generation for each of the population. The effective number of parents in each generation averaged 174 and 187 for male and female populations, respectively. The traits measured were egg number to 280 days (EGG280 D), age at sexual maturity (ASM), egg weight average (EWTAV) and body weight at 40 weeks of age (BWT40). The co-efficient of inbreeding per generation due to finite population size was 0.005 for both the male and the female lines respectively. For the control population the values obtained were 0.008 vs 0.007 for both the male and female lines respectively. The average performance of the birds over the study period for the male and female lines respectively ranged from 38.38 vs 50.94 and 37.03 vs 51.25 for EGG280 D, 194 vs 212 and 197 vs 214 for ASM, 48.29 vs 55.93 and 48.29 vs 55.11 for EWTAV, 1600 vs 1754 and 1440 vs 1908 for BWT40.The effective number of parent in each generation averaging about 175 probably caused an average inbreeding of about 0.5% per generation. Although the level of inbreeding in this population is not critical there is evidence of an increasing trend, which could lead to homozygosity in the flock. There is need to widen the genetic base to prevent selection depression too early in the flock.